2011
DOI: 10.1248/yakushi.131.731
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Pigmentation by Minocycline in Murine B16 Melanoma Cells

Abstract: Long-term treatment with minocycline is known to induce pigmentation or discoloration in tissues but how remains unclear. We investigated the mechanism of pigmentation using B16 melanoma cells. First, we conˆrmed that intracellular melanin levels increased on minocycline treatment. Then, using the reverse transcriptase-polymerase chain reaction (RT-PCR), we found the expression of mRNA of tyrosinase, tyrosinase-related protein (TRP)-1 and TRP-2, to also be signiˆcantly increased by treatment with minocycline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The past two decades have brought an enormous increase in our understanding of melanogenic enzymes, of melanosomes, and of the intracellular and intercellular signaling pathways that regulate pigmentation (Park, Kosmadaki, Yaar, & Gilchrest, 2009). The B16 mouse melanoma cell line is used extensively for melanogenic studies and is considered a stable cell line for studying melanin production (Kim et al, 2014;Sato, Tsukimoto, Shimura, Awaya, & Kojima, 2011;Yao, Oh, Oh, Park, & Chung, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The past two decades have brought an enormous increase in our understanding of melanogenic enzymes, of melanosomes, and of the intracellular and intercellular signaling pathways that regulate pigmentation (Park, Kosmadaki, Yaar, & Gilchrest, 2009). The B16 mouse melanoma cell line is used extensively for melanogenic studies and is considered a stable cell line for studying melanin production (Kim et al, 2014;Sato, Tsukimoto, Shimura, Awaya, & Kojima, 2011;Yao, Oh, Oh, Park, & Chung, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to unambiguously indicate the reason or mechanism for minocyclineinducing redox imbalance. Among the possible causes can be mentioned: (i) direct influence of minocycline on the antioxidant system or ROS production, (ii) the ability of minocycline to induce melanogenesis which could be also the source of ROS, and (iii) the impairment of mitochondrial function by the drug [67,68]. The conducted studies showed that minocycline caused, e.g., mitochondrial depolarization and permeabilized the inner mitochondrial membrane by forming ion channels [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Dutkiewicz, Albert and Levin also reported latanoprost did not increase the mitotic index of human cutaneous melanoma cell lines. When it comes to minocycline‐induced hyperpigmentation, although not completely elucidated, the increase in the expression of tyrosinase, TRP‐1 and TRP‐2 and activation of p38 MAPK are thought to cause the side effect . Further molecular study on latanoprost‐induced hyperpigmentation is worth to practice.…”
Section: Discussionmentioning
confidence: 99%